Peran Usaha Ekonomi Kreatif Dalam Penyerapan Tenaga Kerja Muslim - Ayu Lestari; Zulhelmi Zulhelmi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The creative economy is a form of business that focuses more on people's creativity to create something new or innovate existing goods or businesses so that they have marketability and competitiveness in the market. The existence of the creative economy has a role in creating jobs to accommodate local communities, increase income, preserve culture and encourage export-import. The purpose of this study was to determine the role of the creative economy business of the Independent Young Embroidery and Embroidery House in absorbing Muslim workers. The research method used is descriptive qualitative research, data collection methods by observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. From the results of the research, it was found that the role of the creative economy business Rumah Mandiri Embroidery and Embroidery Young has a role in absorbing Muslim workers, which play a role in providing jobs, increasing income, increasing intellectual property, preserving culture, encouraging product exports. The determining factors considered in absorbing labor are labor wages, skills possessed, investment value, and production value.